Analisis Pelaksanaan Penertiban Pemakaian Tenaga Listrik (P2TL) Sebagai Upaya Penekanan Susut Non Teknis Di PT PLN (Persero) ULP Koba - Amirah Khairunnisah; Amani Darma Tarigan; Rahmaniar Rahmaniar (Elkom: Jurnal Elektronika dan Komputer, 2024)
Electricity theft is an activity that is detrimental to the state where PLN as the party that distributes electricity has unknowingly lost its main commodity without any reciprocity in the form of payment. To overcome electricity theft, Execution of Electricity Use (P2TL) is carried out. Implementation of Electric Power Use (P2TL) is an activity to control electricity users who do not comply with installation standards. P2TL activities include planning, inspection, technical and/or legal actions and settlements carried out by PLN on PLN installations and/or Electric Power User installations. P2TL activities carried out in the Koba area from October to December 2023 found 3 violations in the area. The kWh saved as a result of P2TL from October to December was 21,480 kWh. From the kWh savings obtained, the highest loss was in October of 0.47% and the loss obtained without P2TL kWh savings was 0.48%. So that the kWh savings obtained from P2TL can reduce Non-Technical Losses. The more P2TL violations are found, the higher the reduction in losses obtained by PT PLN (Persero) ULP Koba.